Implementasi Lingkungan Positif yang Mendukung Pembelajaran dan Pengelolaan Kelas di Lingkungan Kelas Enam Salah Satu SDN di Surabaya Barat - Nidaus S, Aulia; Marcelina R, Stevi; Daffa D, Naufal; A. D. P., Tata Desvita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Classroom management is a conscious effort to plan, organize, implement, and supervise programs and activities in the classroom, so that the learning process can run systematically, effectively, and efficiently. Classroom management is needed to optimize the achievement of learning objectives. The essence of good classroom management is to solve problems that interfere with learning with effective strategies. This study aims to determine the professionalism of teachers in one of the elementary schools in Surabaya, the level of professionalism and competence of teachers in creating a positive learning environment, the condition of the student learning environment in the classroom, and the effect of a positive environment at school on student learning success. This research uses a qualitative approach with data collection techniques through observation and documentation. The results show that a positive environment at school supports students' learning success by creating a safe space to interact without judgment and develop interests and talents in learning. The research results include: (1) Teacher professionalism in the classroom, (2) The level of professionalism and competence of teachers in creating a positive learning environment, (3) The condition of the student learning environment in the classroom, (4) The feasibility of facilities and infrastructure that support learning in the classroom, (5) The effect of a positive environment in schools on student learning success in the classroom.